The role of relative fat mass in gallstone risk assessment: findings from the NHANES 2017–2020 survey - Wang, Li; Cao, Shan; Song, Guodong (Frontiers in Nutrition, 2025)
BackgroundGallstones are a prevalent condition that can lead to significant morbidity and healthcare costs. Relative fat mass (RFM), as a potential marker of body fat distribution, may offer insights beyond traditional metrics like body mass index (BMI) and waist circumference. This study aims to investigate the association between RFM and gallstone prevalence in the U.S. population.MethodsThe study cohort comprised 6,881 participants obtained from the National Health and Nutrition Examination Survey (NHANES) conducted between 2017 and 2020. Participants were stratified into quartiles (Q1–Q4) based on their RFM. To evaluate the associations, multivariable logistic regression analyses were employed to assess odds ratios (OR) for gallstone risk across different quartiles of RFM. Additionally, restricted cubic spline analysis was conducted to ascertain the relationship trend while subgroup analyses examined interactions based on age, sex, race, education level, and lifestyle factors.ResultsThe analysis revealed significant associations for participants within the higher RFM quartiles (Q3 and Q4), with ORs of 2.58 (95% CI: 1.65, 4.04) and 6.30 (95% CI: 3.63, 10.93), respectively, compared to Q1. The findings consistently indicated that RFM, particularly in Q4, is a strong predictor of gallstone risk, demonstrating superior predictive performance relative to waist circumference and BMI, as evidenced by an AUC of 0.702.ConclusionElevated RFM is a noteworthy predictor of gallstone risk in the studied population, suggesting its potential utility in clinical risk assessment frameworks. Future research should focus on elucidating the underlying mechanisms driving this association and exploring RFM's applicability as a pragmatic tool in clinical practice for gallstone risk stratification.